1990
DOI: 10.1002/pen.760300807
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric and magnetic properties of random and segregated ferrite polystyrene composites

Abstract: The dielectric and magnetic properties of polystyrene composites containing barium or nickel‐zinc ferrites were studied as function of the ferrite concentration and field frequency. The composites were prepared by methods yielding a random distribution of the ferrite particles or segregated structures. Barium ferrite‐poly‐styrene composites exhibited a typical insulator behavior, and only above 60% ferrite were high values of the dielectric properties noted at the lower frequencies, decreasing gradually with f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
1

Year Published

1992
1992
2014
2014

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 12 publications
1
14
0
1
Order By: Relevance
“…), and polymer/magnetic metal nanocomposites (with metallic Fe, [26] Co, [27] maghemite, [28] and Fe 3 O 4 [29] ) within a polymer matrix. Macroscopic composites of 10±100 lm sized transition metal powders [30] and ferrites [31] have been fabricated in order to study their electrical and magnetic properties. A classification of nanostructure morphologies, according to the mechanism responsible for their magnetic properties, has been proposed.…”
Section: Magnetic Composite Materialsmentioning
confidence: 99%
“…), and polymer/magnetic metal nanocomposites (with metallic Fe, [26] Co, [27] maghemite, [28] and Fe 3 O 4 [29] ) within a polymer matrix. Macroscopic composites of 10±100 lm sized transition metal powders [30] and ferrites [31] have been fabricated in order to study their electrical and magnetic properties. A classification of nanostructure morphologies, according to the mechanism responsible for their magnetic properties, has been proposed.…”
Section: Magnetic Composite Materialsmentioning
confidence: 99%
“…Metal–polymer composites have been the subject of extensive research 1–3. Considerable effort has been expended in the investigation of the structure–property relationship,4–9 at molecular and morphological level, which is necessary for designing new materials with desirable properties for specific technological applications 10–14…”
Section: Introductionmentioning
confidence: 99%
“…The influence of nature, concentration and filler dimensions on the properties of polymer composites with conductive [15][16][17][18] or magnetic [14], [19][20] fillers was studied in several papers. It is shown that there is a critical concentration for that the percolation process occurs, leading to important variations of the electrical conductivity, permittivity and dielectric losses [14], [21][22] and magnetic properties [20].…”
Section: Introductionmentioning
confidence: 99%